Detecting emotion in others: increased insula and decreased medial prefrontal cortex activation during emotion processing in elite adventure racers - Thom, Nathaniel J. (Oxford University Press, 2014)
Understanding the neural processes that characterize elite performers is a first step to develop a neuroscience model that can be used to improve performance in stressful circumstances. Adventure racers are elite athletes that operate in small teams in the context of environmental and physical extremes. In particular, awareness of team member’s emotional status is critical to the team’s ability to navigate high-magnitude stressors. Thus, this functional magnetic resonance imaging (fMRI) study examined the hypothesis that adventure racers would show altered emotion processing in brain areas that are important for resilience and social awareness. Elite adventure racers (n = 10) were compared with healthy volunteers (n = 12) while performing a simple emotion face-processing (modified Hariri) task during fMRI. Across three types of emotional faces, adventure racers showed greater activation in right insula, left amygdala and dorsal anterior cingulate. Additionally, compared with healthy controls adventure racers showed attenuated right medial prefrontal cortex activation. These results are consistent with previous studies showing elite performers differentially activate neural substrates underlying interoception. Thus, adventure racers differentially deploy brain resources in an effort to recognize and process the internal sensations associated with emotions in others, which could be advantageous for team-based performance under stress.